2008
DOI: 10.1002/jbt.20248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper intoxication on rat liver proteasome activity: Relationship with oxidative stress

Abstract: Copper toxicity is associated with formation of reactive oxygen species, which are capable to oxidize proteins. The selective removal of the latter by the 20S proteasome is considered an essential part of the cell antioxidant defense system. The aim of the present study was to investigate whether peptidase activities of rat liver proteasomes were affected by chronic (40 mg CuSO(4)/rat/daily with the drinking water for 2 weeks) and acute (20 mg/kg CuSO(4), s.c.) copper treatment. To evaluate the role of proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…It was attributed to ROS production particularly involvements of hydrogen peroxide in the lipid per oxidation. Our results are also in agreement with an earlier study (54) suggesting that copper significantly increased lipid per oxidation levels in the hepatocytes through ROS generation which may lead to significant elevation in TBARS levels. Concurrently, copper overloads significantly decrease the Superoxide dismutase activity in both copper sulphate treated groups in the brain tissue.…”
Section: Discussionsupporting
confidence: 94%
“…It was attributed to ROS production particularly involvements of hydrogen peroxide in the lipid per oxidation. Our results are also in agreement with an earlier study (54) suggesting that copper significantly increased lipid per oxidation levels in the hepatocytes through ROS generation which may lead to significant elevation in TBARS levels. Concurrently, copper overloads significantly decrease the Superoxide dismutase activity in both copper sulphate treated groups in the brain tissue.…”
Section: Discussionsupporting
confidence: 94%
“…Secondly, when the liver is damaged, it may cause imbalances in blood glucose homeostasis such as glycogen synthesis, gluconeogenesis and transformation, while excessive blood glucose concentration stimulates the CNS, causing abnormal release of GH, ghrelin and NPY, hence inhibiting feeding and growth of pigs (Kmiec, 2001;Pocai, Obici, Schwartz, & Rossetti, 2005). Thirdly, after the oxidative damage of liver cells (Ozcelik, Ozaras, Gurel, Uzun, & Aydin, 2003), the liver's ability to scavenge bacteria, viruses, antigens and denatured proteins in the blood is weakened, therefore making pigs more susceptible to diseases (Alexandrova et al, 2008). Hence, long-term consumption of high copper diets may weaken liver function and inhibit the growth rate of pigs (Figure 3).…”
Section: Livermentioning
confidence: 99%
“…Studies in the liver of rats reported increased oxidative stress damage of proteins and protein degeneration caused by Cu (Alexandrova et al, 2008), lipid peroxidation expressed as MDA activity or immunoreactivity (Zhang et al, 2000;Ozcelik and Uzun, 2009) and DNA damage (Gaetke and Chow, 2003;Alexandrova et al, 2007) that finally could lead to apoptotic cell death (Rana, 2008). Lipid peroxidation produced by ROS is considered to be the most likely mechanism to damage proteins, rather than a direct action of ROS generated by Cu or other metals overload (Yamada et al, 1992;Ogihara et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that diagnosis of chronic Cu toxicity is complicated and that health risk assessment cannot be based solely on Cu chemical analyses (Walker, 1998;Kakkar and Jaffery, 2005). However, little attention was paid to the liver tissue from a histological point of view and when it does, the studies focused in rat tissue or ruminants that were experimentally induced clinical Cu intoxication (Gooneratne et al, 1979;Kumaratilake and Howell, 1987;Alexandrova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation